ATTITUDE OF STUDENT YOUTH TO PHYSICAL EDUCATION AND SPORTS - Permyakiv, A.A.; Porokhnenko А.V. (Pedagogy of Higher and Secondary Education, 2022)
The student’s youth skills for planning leisure forms of their free organization, and the cause of physical training culture, which influences physical exercises have been analyzed.